HERBAL PLANTS - A BOON FOR HEPATOTOXICITY - Chaudhary, Preeti; Ahmad, Shamim; Ali Khan, Najam (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Liver diseases have become one of the major causes of morbidity and mortality all over the world. From among, drug-induced liver injury is one of the most common causative factors that possess a major clinical and regulatory challenge. Herbal plants have been used traditionally by herbalist worldwide for the prevention and treatment of liver disease. Herbal medicines have recently attracted much attention as alternative medicines useful for treating or preventing lifestyle related disorders and relatively very little knowledge is available about their mode of action. There has been a growing interest in the analysis of plant products which has stimulated intense research on their potential health benefits. Allopathic drugs cause toxicity to the liver by elevating the levels of various biomarkers present in the liver. At present, no single allopathic drug is available in the market for liver damage. Only Liv.52 and silymarin are herbal medicine for this purpose, so herbal drugs have a strong potential in the treatment of liver diseases. The herbal market, in the recent times, is growing day by day and is accepted at the global level. The present review focused on different herbal plants that have been tested for hepatotoxicity in different animal models. Keywords: Hepatoprotective activity, Liver, Hepatotoxicity, Serum enzymes, Silymarin, Liv.52, Herbal plants.